The Principle of Legality in International and Comparative Criminal Law - Gallant, Kenneth S (Cambridge University Press, 2013)
In this book a number of inconsistencies of spelling, capitalization, and typeface appear. Where quoting from or citing to written sources, it uses the spelling of the original source. This being the case, one may well find judgment and judgement, offense and offence, defense and defence, recognize and recognise, Quran and Koran, crimes against humanity, Crimes against Humanity and Crimes Against Humanity, and other inconsistencies scattered throughout this book.